Decentring Anthropocentric Narcissism: The Novum and the EcoGothic in Cixin Liu’s The Three-Body Problem and Ball Lightning - Dories, Jeff (SARE: Southeast Asian Review of English, 2022)
Abstract: This article examines Cixin Liu’s The Three-Body Problem and Ball Lightning using the framework of Liu’s essay “Beyond Narcissism: What Science Fiction Can Offer Literature,” as well as the idea of the ecogothic, as outlined by William Hughes, Andrew Smith, David Del Principe, and Emily Carr. Liu discusses the idea that literature primarily focuses on human relationships. He then explains that the universe is vast, and in the 13.2 billion years of history, humans have only been present for a small percentage of that time. Because of this, he calls for literature to experiment with challenging anthropocentric thought. This article focuses on how Liu uses ecological horror, feelings of dislocation, disorientation, fragmentation, and the uncanny to challenge anthropocentric ideology. It relies on close reading and an examination of intertextuality, especially focusing on Rachel Carson’s Silent Spring and Peter Singer’s Animal Liberation.